Failure rate calculation method for high power devices in space applications at low earth orbit - D, Erdenebaatar; H, Shohei; Sh, Yuji; S, Masaki; O, Ichiro (Scientific transaction of the National University of Mongolia. Physics, 2022)
In this paper we propose that calculation method to evaluate failure rate of high power semiconductor device against proton flux environment of low earth orbit. Advantage of this method is to expand to evaluate failure rate of any devices under various radiation environment. Possible suggestion to improve high power device reliability was discussed.